HISTOMORPHOLOGICAL SPECTRUM AND IMMUNOHISTOCHEMICAL EXPRESSION OF S100 AND CD56 AMONG TUMORS OF PERIPHERAL NERVES-A CROSS-SECTIONAL STUDY - KARTHIK SIGAMANI; SHOBANA B; NAYANA CHANDRAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Peripheral nerve sheath tumors (PNSTs) encompass a range of distinct clinicopathological entities, from benign tumors such as schwannoma to high-grade malignant neoplasms known as malignant PNST (MPNST). Despite having classic, recognizable microscopic features, these neoplasms can occasionally be difficult to diagnose. Immunohistochemistry (IHC) using a panel of markers like S100 and CD56 is helpful in arriving at the correct diagnosis. Methods: This was a cross-sectional study based on laboratory records. All the cases of peripheral nerve sheath tumors reported between January 2021 and December 2021 were retrieved and IHC using S100 and CD56 was carried out. The results were tabulated by scoring the intensity and extent of IHC staining. Results: Neurofibromas and schwannomas did not differ significantly in terms of patient age or the anatomical sites of these tumors. CD56 was positive in the majority of neurofibromas (90%) compared to schwannomas (80%), whereas S100 was positive in all cases of schwannomas (100%) in comparison to neurofibromas (95%). There was a statistically significant difference in the staining intensity of CD56 more for neurofibromas (p=0.015) and that of S100 more for schwannomas (p=0.04). Conclusion: CD56 and S100 IHC analysis will be a helpful supplementary tool for the histopathologist to distinguish peripheral nerve sheath tumors from other soft tissue tumors.